New data of morphological variation in Pulchrana glandulosa (Boulenger, 1882) (Anura: Ranidae) from West Sumatra: Data terbaru variasi morfologi Pulchrana glandulosa (Boulenger, 1882) (Anura: Ranidae) dari Sumatera Barat - Ferix Riskierdi; Rijal Satria; Yusni Atifah; Fitra Arya Dwi Nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Abstract Pulchrana glandulosa is a frog from the family Ranidae which was described in 1882 by Boulenger with the Latin name Rana glandulosa. In his research, Boulenger described this species as having a size range of 48-83 mm in female individuals and 80-92 mm in male individuals. Meanwhile, in Das et al. as of 2007, this species measures 93 mm. The difference in size in the morphology of a species can be influenced by the environment where the species originates and the number of samples used also affects the size range obtained. For West Sumatra itself, research related to the morphology of P. glandulosa has never been done. Therefore, this study aims to provide the latest information on variations in the morphological characteristics of P. glandulosa in West Sumatra. The research method used is the Visual Encounter Survey/VES by exploring the research location from 20.00-23.00 WIB. The sample used was 12 individuals who were analyzed morphologically and morphometrically (18 characters), then compared with the holotype and paratype of P. glandulosa. The results of this study indicated that the P. glandulosa sample from West Sumatra was smaller than the P. glandulosa holotype; the length and width of the head in the sample, holotype and paratype are not much different; while the mouth length of the sample is larger than the holotype and paratype as well as the interorbital distance and the length of the first toe of the forelegs as a whole are still within the range that has been described. In other morphometric measurements, there are several individuals that are smaller than the holotype and paratype. And overall the measurement of the third and fifth toes of the hind legs is smaller than the holotype and paratype of P. glandulosa. Keywords: Morphological Study, Morphological Variation, Anura, Taxonomy, VES Abstrak Pulchrana glandulosa merupakan salah satu katak dari family Ranidae yang dideskripsikan pada tahun 1882 oleh Boulenger dengan nama latin Rana glandulosa. Dalam penelitiannya Boulenger mendeskripsikan spesies ini memiliki rentang ukuran 48-83 mm pada individu betina dan 80-92 mm pada individu jantan. Sedangkan pada penelitian Das et al. pada 2007, spesies ini memiliki ukuran 93 mm. Perbedaan ukuran pada morfologi suatu spesies tersebut dapat dipengaruhi oleh lingkungan dimana spesies itu berasal dan jumlah sampel yang digunakan juga berpengaruh terhadap rentang ukuran yang didapatkan. Untuk Sumatera Barat sendiri, penelitian terkait morfologi dari P. glandulosa belum pernah dilakukan. Oleh karena itu, penelitian ini bertujuan untuk memberikan informasi terbaru variasi karakteristik morfologi P. glandulosa di Sumatera Barat. Metode penelitian yang digunakan adalah Visual Encounter Survey/VES dengan melakukan penjelajahan pada lokasi penelitian mulai dari pukul 20.00-23.00 WIB. Sampel yang digunakan berjumlah 12 individu yang dianalisis secara morfologi dan morfometri (18 karakter), kemudian dibandingkan dengan holotype dan paratype P. glandulosa. Hasil dari penelitian ini menunjukkan bahwa sampel P. glandulosa dari Sumatera Barat berukuran lebih kecil dibandingkan holotype P. glandulosa; panjang dan lebar kepala pada sampel, holotype dan paratype tidak jauh berbeda; sedangkan panjang mulut sampel berukuran lebih besar dibandingkan holotype dan paratype serta jarak interorbital dan panjang jari pertama kaki depannya secara keseluruhan masih dalam rentang yang telah dideskripsikan. Pada pengukuran morfometri lainnya terdapat beberapa individu yang memiliki ukuran lebih kecil dibandingkan holotype dan paratype. Dan secara keseluruhan pada pengukuran jari ketiga dan kelima kaki belakang memiliki ukuran lebih kecil dibandingkan holotype dan paratype P. glandulosa. Kata Kunci: Studi Morfologi, Variasi Morfologi, Anura, Taksonomi, VES